Successful combination therapy of propranolol and prednisolone for a case with congenital Kasabach–Merritt syndrome. Issue 12 (3rd August 2017) - Mizutani, Kento; Umaoka, Ai; Tsuda, Kenshiro; Kakeda, Masato; Habe, Koji; Yamanaka, Keiichi; Suyama, Megumi; Mizutani, Hitoshi
Abstract: A male fetus was delivered by cesarean section with a large hemangioma on his right chest and thrombocytopenia. Clinically, Kasabach–Merritt syndrome (KMS) was suspected, and immediately he was treated with daily prednisolone (PSL) 1 mg/kg and recombinant thrombomodulin without response. Additional propranolol (1–3 mg/kg per day) and increased PSL 2 mg/kg per day therapy successfully controlled his disseminated intravascular coagulation and decreased the tumor size without serious side‐effects. No relapse of KMS was observed after cease of PSL and propranolol. Combined use of propranolol and corticosteroid is expected as a candidate therapeutic tool for KMS.